Cementless Total Hip Arthroplasty with Large Diameter Metal-on-Metal Heads: Short-Term Survivorship of 8059 Hips from the Finnish Arthroplasty Register. (June 2013) - Mokka, J.; Mäkelä, K. T.; Virolainen, P.; Remes, V.; Pulkkinen, P.; Eskelinen, A.
Background and Aims: Population-based register data from the National Joint Register of Australia and England and Wales have revealed that the mid-term outcome of cementless large diameter head metal-on-metal total hip arthroplasty is inferior to that of conventional cemented metal-on-polyethylene total hip arthroplasty. The aim of this study was to compare the results of cementless large diameter head metal-on-metal total hip arthroplasty with conventional cemented arthroplasty in Finland. The second aim of this study was to compare the cementless large diameter head metal-on-metal models with each other. Material and Methods: Based on the data extracted from the Finnish Arthroplasty Register, the risk of revision of 8059 cementless large diameter head metal-on-metal total hip arthroplasties performed during 2002–2009 was analyzed using Cox regression model. The revision risk of these hips was compared to that of 16, 978 cemented metal-on-polyethylene total hip arthroplasties performed during the same time period. Results: In the Cox regression analysis, there was no difference in revision risks between cementless large diameter head metal-on-metal total hip arthroplasty and cemented metal-on-polyethylene total hip arthroplasty (relative risk = 0.90, confidence interval = 0.74–1.10, p = 0.3). However, in female patients aged 55 years or above, cementless large diameter head metal-on-metal total hip replacements showed a significantly increased risk of revision as compared to cemented total hip replacements (relative risk = 1.33, confidence interval = 1.04–1.70). Compared to the reference implant in this study (cementless Synergy stem combined with Birmingham Hip Resurfacing [BHR] cup), the CementLess Spotorno (CLS) stem combined with Durom cup had a 2.9-fold (95% confidence interval = 1.17–6.90) increased risk of revision. Conclusions: We found that cementless large diameter head metal-on-metal total hip arthroplasty had short-term survivorship compared with cemented total hip arthroplasty at a nation-wide level. However, in female patients aged 55 years or above, cementless large diameter head metal-on-metal total hip arthroplasty showed inferior results. Furthermore, implant design had an influence on revision rates. Longer follow-up time is needed to assess the success of large diameter head metal-on-metal total hip arthroplasty.